Baseline health and public healthcare costs five years on: A predictive analysis using biomarker data in a prospective household panel - Apostolos Davillas; Stephen E. Pudney (University of Essex, Institute for Social and Economic Research (ISER), 2019)
We investigate the utilisation of primary and secondary public healthcare services and the consequent public costs, using data from the British Understanding Society household panel. We use a sample of 2,314 adults who, at baseline in 2010/11, reported no history of diagnosed long-lasting health conditions and for whom a set of objective biomarkers were observed. Five years later, their utilisation of GP and hospital outpatient and inpatient services was observed. We develop an econometric technique for count data observed within ranges and a method of combining NHS episode cost data with Understanding Society data without exact individual-level matching. This allows us to estimate the impact of differences in personal characteristics and socio-economic status (SES) on cost outcomes. We find that a composite biomarker index approximating allostatic load is a powerful predictor of realised costs: among the group who are at least 1 standard deviation (SD) above mean allostatic load, we estimate that a reduction of 1 SD at baseline reduces GP, outpatient and inpatient cost outcomes by around 18%. In addition to the expected strong effect of ageing on cost, we also find a large gender difference: on average women experience costs at least 20% higher than comparable men, because of their greater utilisation of GP and outpatient services. There is a strong SES gradient in healthcare costs: the average impact of moving from no educational qualifications to intermediate or from intermediate to degree level is approximately 16%. Income differences, on the other hand, have negligible impact on future costs.
Keywords: C3; C8; I10; I18; 330; Healthcare costs; Socioeconomic gradient; Biomarkers; Allostatic load; Understanding Society